2018
DOI: 10.1007/s12039-017-1410-3
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and evaluation of mesoporous nickel and manganese bimetallic nanocatalysts in methane dry reforming process for syngas production

Abstract: In this paper, Ni-Mn catalysts supported on mesoporous nanocrystalline γ-Al 2 O 3 were prepared and employed in carbon dioxide reforming of methane for the production of synthesis gas. The physicochemical properties of the catalysts were determined by XRD, BET, TPO and SEM techniques. The obtained results revealed that the Mn-promoted catalysts exhibited higher activity and stability and lower degree of carbon formation compared to unpromoted nickel catalyst. The catalytic results showed that the 10 (wt%) Ni-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…Using CO2-TPD measurements, the authors showed that higher Mn content (10%) prompted better CO2 adsorption. In addition to the superior promotion of both CO2 and CH4 on the surface of our synthesized materials, we envisage that the presence of an in-situ elimination of carbon via Mn3O4/C/MnO/CO2 redox looping cycle could play a synergetic role which can lead to lowering the amount of surface carbon during the reaction of CO2 reforming of methane [40][41][42]. Where carbon residues are formed on the surface of reduced Ni particles, migration of carbon to neighboring Mn3O4 sites could be anticipated to enable the in-situ elimination of carbon.…”
Section: Influence Of Mn Position On Catalyst Stability and Carbon Fomentioning
confidence: 99%
“…Using CO2-TPD measurements, the authors showed that higher Mn content (10%) prompted better CO2 adsorption. In addition to the superior promotion of both CO2 and CH4 on the surface of our synthesized materials, we envisage that the presence of an in-situ elimination of carbon via Mn3O4/C/MnO/CO2 redox looping cycle could play a synergetic role which can lead to lowering the amount of surface carbon during the reaction of CO2 reforming of methane [40][41][42]. Where carbon residues are formed on the surface of reduced Ni particles, migration of carbon to neighboring Mn3O4 sites could be anticipated to enable the in-situ elimination of carbon.…”
Section: Influence Of Mn Position On Catalyst Stability and Carbon Fomentioning
confidence: 99%
“…159 The high hydrogen dissociation capacity of the noble metals might be a factor in the high activity of the catalysts. The addition of a second metal was also found to improve the Ni dispersion in several alloys (Mn-Ni, 97,98 Co-Ni, 116 Rh-Ni, 76 Ir-Ni, 83 Pt-Ni, 84 etc.). As discussed in chapter 3, the Ni particle size has a significant effect on the ease of carbon deposition.…”
Section: Summary and Perspectivesmentioning
confidence: 94%
“…Mn-Ni. Recently, Najfach et al, 97 and Ramezani et al 98 reported effects of Mn to Ni catalysts. They described effects of increased Ni dispersibility, which led to less coke formation.…”
Section: Addition Of the Base Metal To Ni Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“….São inúmeras as finalidades industriais das bentonitas e movimentam centenas de milhares de dólares no mercado global a cada ano. Sua aplicação em diversos processos é justificada pelas suas propriedades, que são: elevada área superficial, capacidade adsorvente, propriedades reológicas, pureza química e toxicidade baixa ou inexistente (SILVA FAVERO, 2019).Com características específicas, como boa seletividade, estabilidade química, menor custo e grande disponibilidade, as bentonitas têm sido amplamente utilizadas em aplicações industriais como suportes e catalisadores(LI, 2012;RAMEZANI;MESHKANI;.…”
unclassified